2002
DOI: 10.1017/s003118200100107x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ehrlichia phagocytophila transmission coefficients from sheep ‘carriers’ to Ixodes ricinus ticks vary with the numbers of feeding ticks

Abstract: In a longitudinal study in a UK upland site, 38% of adult sheep were detected as infected with the tick-borne bacterium Ehrlichia phagocytophila by PCR of blood samples. Infection prevalence declined significantly with sheep age but varied significantly and non-linearly with the number of adult Ixodes ricinus ticks feeding per sheep. These findings suggested that under conditions of natural repeated tick-borne challenge sheep remain partially susceptible to re-infections, but the likelihood of re-infection dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 25 publications
1
34
1
1
Order By: Relevance
“…However, in none of the animals were obvious clinical signs apparent. The infection rate of 4% in German sheep was somewhat lower than those reported from other countries such as the United Kingdom (38%), Italy (18%), and Turkey (18%) (25,43,67). In contrast, 94% of the German roe deer investigated were positive for A. phagocytophilum, whereas the infection rate in neighboring European states was between 18 and 88% (18,36,44,46,53,56,77).…”
Section: Discussionmentioning
confidence: 53%
“…However, in none of the animals were obvious clinical signs apparent. The infection rate of 4% in German sheep was somewhat lower than those reported from other countries such as the United Kingdom (38%), Italy (18%), and Turkey (18%) (25,43,67). In contrast, 94% of the German roe deer investigated were positive for A. phagocytophilum, whereas the infection rate in neighboring European states was between 18 and 88% (18,36,44,46,53,56,77).…”
Section: Discussionmentioning
confidence: 53%
“…One millilitre of diluted stabilate of each isolate was inoculated intravenously into one susceptible sheep bred and maintained in a tick-free environment. Blood samples were used to monitor infection by microscopy of Giemsa-stained smears and PCR (Ogden et al, 2002). DNA extracted from blood samples collected during the second day of bacteraemia was used for the amplification and sequencing of the 16S rRNA gene and the p44 gene as described below.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from the engorged tick by alkaline digestion as previously described (Ogden et al, 2002). A nested PCR was used to amplify a 546 bp region of the 16S rRNA gene of A. phagocytophilum (Massung et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The role of sheep in the natural maintenance of A. phagocytophilum has been studied in some detail, and it is clear that in some settings they serve as its main reservoir. For instance, Ogden and colleagues (21,22) demonstrated the maintenance of A. phagocytophilum in "fell"-grazing sheep flocks in the absence of other important hosts such as rodents or deer. Early studies revealed that A. phagocytophilum infections can persist for several months or longer in sheep (15), and more recent experimental studies have further quantified their dynamics (11,31).…”
mentioning
confidence: 99%